An Equivalent Definition for the Backwards Ito Integral: Jayrold P. Arcede, Emmanuel A. Cabral - Team, Support (Thai Journal of Mathematics, 2011)
This paper aims to give an equivalent definition of backwards Ito integral that considers a full division on a compact interval [a,b].